Dampak Embargo Gas Rusia Terhadap Transisi Energi di Jerman Tahun 2022 - Fadhil Rachmanda; Ali Muhyidin; Muhammad Imam (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This research discusses how the Russian gas embargo to Germany as a result of the Russia-Ukraine conflict impacts the energy transition policy in Germany. By using qualitative methods and collecting data from secondary data, this research sees that the energy transition policy or energiewende carried out by the German government occurs not only because of external factors, but also internal factors, namely increasing concern for the environment and energy security. Energiewende is not an easy step to take, because Germany is still dependent on Russian gas. Researchers found that Germany can maintain energy stability by adapting policies by implementing several alternative policies, one of which is the temporary activation of coal-fired power plants while taking other preventive measures.